Low temperature magnetic properties of the Late Archean Boolgeeda iron formation (Hamersley Group, Western Australia): environmental implications - Carlut, Julie; Isambert, Aude; Bouquerel, Hélène; Pecoits, Ernesto; Philippot, Pascal; Vennin, Emmanuelle; Ader, Magali; Thomazo, Christophe; Buoncristiani, Jean-François; Baton, Frank; Muller, Elodie; Deldicque, Damien (Frontiers in Earth Science, 2015)
The origin of the iron oxides in Archean and Paleoproterozoic Banded Iron Formations is still a debated question. We report low and high temperature magnetic properties, susceptibility and saturation magnetization results joined with scanning microscope observations within a 35 meters section of the Late Archean Boolgeeda Iron Formation of the Hamersley Group, Western Australia. With the exception of two volcanoclastic intervals characterized by low susceptibility and magnetization, nearly pure magnetite is identified as the main magnetic carrier in all iron-rich layers including hematite-rich jasper beds. Two populations of magnetically distinct magnetites are reported from a 2 meter-thick interval within the section. Each population shows a specific Verwey transition temperature: one around 120-124 K and the other in the range of 105-110 K. This temperature difference is interpreted to reflect two distinct stoichiometry and likely two episodes of crystallization. The 120-124K transition is attributed to nearly pure stoichiometric magnetite, SEM and microprobe observations suggest that the lower temperature transition is related to chemically impure silician magnetite. Microbial-induced partial substitution of iron by silicon is suggested here. This is supported by an increase in Total Organic Carbon (TOC) in the same interval.